Looking into the knowledge and attitudes of nurses regarding mourning and burial customs of people with different cultural background - Areti Papadopoulou; Paraskevi Apostolara; Petros Galanis; Athina Kalokairinou (Ene, 2018)
Introduction: Death is an uncomfortable situation for everyone. Due to the nature of nursing profession, a nurse comes everyday face to face with death. Undoubtedly, this is a difficult procedure that becomes even more difficult when the deceased has a different cultural or ethnic background. Aim: The aim of the study was to examine the knowledge and attitudes of nurses regarding mourning and burial customs of persons from different cultural backgrounds. Additionally, the study aimed to examine the source of health professionals' knowledge and the degree of their intention to learn the burial customs and different ways of mourning of different cultures. Methods: This is a cross-sectional study with a convenience sample of 181 nurses employed in the General Hospital of Volos. Due to the lack of a questionnaire adapted and suitable to the needs of the Greek population, a new one was created, based on similar international studies. A pilot study with 30 participants was conducted. The level of significance was bilateral and the statistical significance was set at 0.05. Statistical analysis was performed with SPSS 19.0 statistical program. Results: It emerged from the study that there is a significant positive correlation between the attitude scores and the knowledge of the participants regarding the burial customs and the way of mourning of people with different cultural backgrounds. So, the higher the knowledge the participants had, the more positive was their attitude (p=0,020). It was found that nurses working in a ward with specific protocols about care after death for different cultures had more positive attitude compared to nurses who worked in wards with no such protocol (p=0,012). Furthermore, participants who had been taught, at undergraduate level, about after death multicultural care procedures had significantly more knowledge and more positive attitude compared to participants who had not received such training (p=0,001). Finally, 44.2% of the participants wanted "considerably/very much" to be trained in topics of care and burial customs of people from different cultural backgrounds. Conclusions: Greece in the last twenty years has become a multicultural country. It is needed for healthcare schools to include in their syllabus more courses related to death and care for the end of life, so that healthcare professionals could acquire the appropriate knowledge and become competent to care for the dying patient with respect to his/her right of a dignified death.